Association Between Patterns of Electronic Cigarette Use and Recurrent Bronchitis Among Young Adults - Sultan, Dharma; Setyawan, Yuswanto (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Electronic cigarette use has become increasingly prevalent among young adults, raising concerns about its potential impact on respiratory health. This study aimed to investigate the association between patterns of electronic cigarette use and the occurrence of recurrent bronchitis symptoms in young adults. A quantitative analytic study with a cross-sectional approach was conducted involving 150 respondents aged 18–25 years. Participants were selected using purposive sampling, and data were collected through structured questionnaires. The variables measured included frequency of e-cigarette use and incidence of recurrent bronchitis symptoms. Data analysis involved Chi-square tests and Spearman correlation to examine the relationship between vaping patterns and respiratory complaints. The results showed a significant association between frequent e-cigarette use (≥4 times per week) and the presence of recurrent bronchitis symptoms, with a Spearman correlation value indicating a strong positive relationship. Regular users were found to be four times more likely to experience bronchitis than occasional or non-users. These findings suggest that habitual vaping may lead to bronchial irritation and inflammation, contributing to the onset of recurrent bronchitis. In conclusion, frequent electronic cigarette use poses a substantial risk to respiratory health among young adults and warrants greater public health attention.